Afterword: Court Records and the Growth of States 1100–1800. Issue 1 (21st November 2019) - Forrest, Ian
An afterword to the special collection 'New Approaches to Medieval Court Records'. The piece reflects on the role of law courts in medieval and early modern state formation, and offers critical assessment of the state of the field, examining chronological and geographical limitations to current scholarship.